2019
DOI: 10.1055/s-0039-1678683
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Recurrent DVT of the Leg by Two Different Non–Contrast-Enhanced Magnetic Resonance Direct Thrombus Imaging Techniques: A Pilot Study

Abstract: Introduction Magnetic resonance direct thrombus imaging (MRDTI) is a promising technique to improve the diagnostic management of patients with a suspected ipsilateral recurrent deep vein thrombosis (DVT) by direct visualization of a thrombus. Another magnetic resonance imaging (MRI) technique, T1-weighted turbo spin-echo spectral attenuated inversion recovery (TSE-SPAIR), has the potential to image a thrombus directly with a high spatial resolution as well. The main aim of this pilot study was to investigate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…High accuracy of ultrasound and CT for diagnosis of DVT in lower extremities has been reported. 5 Additionally, previous studies showed that MR direct thrombus imaging, based on T1WI, can detect recurrent DVT [8][9][10] and accurately detect pelvic vein thrombosis in pregnancy. 28 In our study, IVC/pelvic thrombi, incidental, and recurrent DVT were detected by MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High accuracy of ultrasound and CT for diagnosis of DVT in lower extremities has been reported. 5 Additionally, previous studies showed that MR direct thrombus imaging, based on T1WI, can detect recurrent DVT [8][9][10] and accurately detect pelvic vein thrombosis in pregnancy. 28 In our study, IVC/pelvic thrombi, incidental, and recurrent DVT were detected by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance (MR) diffusion-weighted imaging (DWI) is noninvasive, and it relies on detecting the random motion of free water molecules. Although several reports have indicated that MR imaging (MRI) is useful for diagnosing DVT, [6][7][8][9][10] a method of defining thrombus age has not been established. The present study aimed to determine whether DWI can detect venous thrombi in patients with DVT, and define thrombus age in a rabbit model compared with histological findings.…”
Section: Introductionmentioning
confidence: 99%
“…In all patients with confirmed (group 1) or excluded UEDVT (group 2) MR‐NCTI, including both MRDTI and 3D‐TSE SPAIR sequences, was performed within 48 h of the initial diagnosis. MRI scans were performed with a 1.5 or 3.0 Tesla unit using an integrated 16‐channel posterior coil and a 16‐channel anterior body coil for signal reception 9,10,17 1.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary studies suggest that 18F-fluorodeoxyglucose positron emission tomography/CT (FDG-PET/CT) and magnetic resonance direct thrombus imaging (MRDTI) may be useful for the diagnosis of recurrent DVT. FDG-PET/CT has the potential to differentiate new thrombus from old thrombus because of the preferential uptake of fluorodeoxyglucose by the inflammatory cells that accumulate in newly formed clots 67 , 68 , whereas MRDTI detects the paramagnetic signal induced by release of methemoglobin from fresh thrombus 69 , 70 . In a small prospective study that included 39 patients with recurrent DVT confirmed by the presence of a new non-compressible venous segment on ultrasonography and 42 asymptomatic patients with residual vein occlusion after an index DVT at least 6 months earlier, MDRTI had 95% sensitivity and 100% specificity for detecting recurrent DVT 70 .…”
Section: Uncertainties In Venous Thromboembolism Diagnosismentioning
confidence: 99%